SOME PROBLEMATIC ISSUES OF COMPLIANCE WITH THE PRINCIPLE OF INDEPENDENCE OF LAWYER ACTIVITY IN THE ASPECT OF COMPULSORY MEMBERSHIP IN THE UKRAINIAN NATIONAL BAR ASSOCIATION - Заборовский, Виктор Викторович (Teisė, 2017)
Article is devoted to the legal nature of the professional associations of lawyers and membership of the Bar Association. The special attention given to the analysis of the European Court of Human Rights and the provisions of international standards of the legal profession. The conclusion, according to which the counsel is obligatory membership UNBA, not only violates the principle of independence of the lawyer activity but there are a prerequisite for the possible existence of an independent legal status.